“CAN YOU IMAGINE, A REAL, LIVE INDIAN RIGHT HERE IN WALNUT GROVE?”: AMERICAN INDIANS IN TELEVISION ADAPTATIONS OF LITTLE HOUSE ON THE PRAIRIE - Fatzinger, Amy S. (Dialogue, 2(1), 2015)
Laura Ingalls Wilder’s Little House novels have been adapted into two major television series: Michael Landon’s well-known series, which aired from 1974-1983, and a more recent Disney adaptation, which aired as a miniseries in 2005. The premier movie, which preceded Landon’s series, and the Disney miniseries both focus on the events in Wilder’s 1935 novel, Little House on the Prairie, which covered the period from 1869-1871 during which the Ingalls family lived among the Osage in Kansas Indian Territory. Wilder’s portrayal of the Osage in her novel is controversial, but she does also include some literary devices that allow for a slightly more complex reading of the relationships between Native and non-Native settlers on the Kansas prairie. While adaptations of novels sometimes revise problematic or controversial content to better suit the perspectives of modern viewing audiences, the adaptations of Wilder’s novels alter the Native content in ways that do not move it beyond the realm of stereotypes. Both television adaptations present Native themes in ways that initially heighten the sense of fear associated with Native characters, then resolve the issues through happy endings and heavy-handed moral lessons that diminish the seriousness of the historic tensions between Native and non-Native residents of the frontier. The changes made to Native themes in the adaptations do, however, call attention to the challenges associated with adapting autobiographical and historical content and raise questions about how to prioritize more respectful portrayals of Native people when working with people’s life stories. Keywords: Little House on the Prairie, American Indian Studies, Pioneer Literature, Historical Fiction, Adaptation Studies, Television Studies
Keywords: Type of access: Open Access